Philosophy and the contemporary educational challenges... - Severino, Antonio Joaquim (Revista Hipótese, 2015)
The purpose of the essay is to explain some elements to reflect on how essential is the mediation of Philosophy in social and cultural frames of contemporary society, in spite of the profound changes that this society has undergone in entry times in the third millennium. The extensive and intense transformations drawing a new scenario for human culture, far from discarding the philosophical training contribution, make it even more necessary. It defends, then, that imposes more than ever, fertilize education with a permanent debate on the ethical, political, aesthetic, epistemological and anthropological. It reaffirms the mission par excellence of education in general and university education in particular in order to ensure that professionals that enables a comprehensive education that goes beyond mere technical expertise. Although assuming a universal perspective, reflection is guided in particular the concrete situation of the sociocultural context of contemporary Brazilian reality.